2000
DOI: 10.1210/endo.141.4.7413
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Ingestion Inhibits the Increased Secretion of Puberty-Related Hormones in the Developing Female Rhesus Monkey*

Abstract: Alcohol (ALC) use and abuse by adolescents has been rising at an alarming rate. Whether ALC consumption during prepubertal years affects specific hormones and the process of sexual maturation is not known. We used immature female rhesus macaques to assess the effects of ALC on circulating levels of hormones known to be critical for the pubertal process. Ten monkeys averaging 20.3 +/- 0.3 months of age were bled by saphenous vein puncture at 0830 and 2030 h each day for 5 consecutive days to determine baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Interestingly, a recent study, in which ALC was administered to prepubertal female rats for 6 days using a specific liquid diet regimen, showed that this more chronic exposure to the drug caused suppression in basal KiSS-1 gene expression, an action that was associated with suppressed basal phosphorylated Akt protein expression (Srivastava et al, 2009). In that study, the ALC also caused suppressed levels of IGF-1 and E 2 , which is associated with ALC-induced delayed purberty and is common following extended exposure to the drug (Dees et al, 2000; Srivastava et al, 1995). It was not possible in that chronic study to discern whether the longer exposure to ALC altered Akt and KiSS-1 expressions by a direct hypothalamic action on the affected neurons, or acted indirectly, as a result of a low IGF-1 signal.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Interestingly, a recent study, in which ALC was administered to prepubertal female rats for 6 days using a specific liquid diet regimen, showed that this more chronic exposure to the drug caused suppression in basal KiSS-1 gene expression, an action that was associated with suppressed basal phosphorylated Akt protein expression (Srivastava et al, 2009). In that study, the ALC also caused suppressed levels of IGF-1 and E 2 , which is associated with ALC-induced delayed purberty and is common following extended exposure to the drug (Dees et al, 2000; Srivastava et al, 1995). It was not possible in that chronic study to discern whether the longer exposure to ALC altered Akt and KiSS-1 expressions by a direct hypothalamic action on the affected neurons, or acted indirectly, as a result of a low IGF-1 signal.…”
Section: Discussionmentioning
confidence: 74%
“…Over the years we have shown that both acute and chronic ALC exposure alters IGF-1 signaling and causes suppressed LHRH/LH secretion and altered pubertal development in both rats and rhesus monkeys (Dees et al, 2000; Hiney et al, 1998; Srivastava et al, 1995). The KiSS-1/GPR54 system is also an important signaling component controlling LHRH secretion and the time of puberty in rats, rhesus monkeys and humans (Navarro et al, 2004a; 2004b; Seminara et al, 2003; Shahab et al, 2005; Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SK3 subunit gene expression can be increased through estrogen receptor activation in vitro (Bosch et al, 2002; Jacobson et al, 2003), and SK2 subunit gene expression can be decreased by glucocorticoids acting through NFκβ (Kye et al, 2007). Although acute estrogen can positively influence alcohol seeking (Ford et al, 2004), long-term alcohol exposure can reduce estrogen function (Dees et al, 2000). A similar pattern is apparent for NFkB (Okvist et al, 2007) and perhaps other regulators of gene expression such as CREB (Spanagel, 2009).…”
Section: Discussionmentioning
confidence: 99%